Prevalence and correlates of severe under-5 child anthropometric failure measured by the composite index of severe anthropometric failure in Bangladesh - Chowdhury, Mohammad Rocky Khan; Khan, Hafiz T. A.; Rashid, Mamunur; Mondal, Md. Nazrul Islam; Bornee, Farzana Akhter; Billah, Baki (Frontiers in Pediatrics, 2022)
Background: Although Bangladesh has made noticeable progress in reducing the prevalence of stunting, wasting, and being underweight among under-5 children, it has not been very successful in reducing overall severe anthropometric failure (SAF) among them. Therefore, the study aims to identify the prevalence and risk factors of SAF measured by the Composite Index of Severe Anthropometric Failure (CISAF) among under-5 children in Bangladesh. Methods: Data was drawn from a cross-sectional Bangladesh Demographic Health Survey (BDHS) conducted in 2017-18. A bivariate analysis (Chi-square test) and logistic regression analysis were used to estimate the unadjusted age and sex-adjusted prevalence of SAF. Odds ratio (OR) and confidence interval (CI) were assessed using logistic regression analysis to identify the various risk factor of SAF. Results: The overall adjusted prevalence of under-5 child SAF was 11.3% (95% CI: 10.6 – 12.0) and it was highly prevalent among children of uneducated mothers (adjusted, 22%, 95% CI: 17.3 – 26.8). The key factors associated with SAF were children in the age group 24-35 months (OR: 2.43, 95% CI: 1.83 – 3.23), children born with low birth weight (OR: 3.14, 95% CI: 2.24 – 4.97), children of underweight mothers (OR: 1.82, 95% CI: 1.44 – 2.29), children of parents with no formal education (OR: 2.28, 95% CI: 1.56 – 3.31) and children from lower socio-economic status (OR: 2.25, 95% CI: 1.55 – 3.26). Conclusion: Prioritizing and ensuring context-specific interventions addressing individual, community, public policy, and environment level risk factors from policy level to implementation to reduce structural and intermediary determinants of under-5 SAF.